2002
DOI: 10.1088/0031-9155/47/14/301
|View full text |Cite
|
Sign up to set email alerts
|

Organ dose conversion coefficients for external photon irradiation of male and female voxel models

Abstract: New organ equivalent dose conversion coefficients are presented for whole body irradiation with monoenergetic photons of energies between 10 keV and 10 MeV for idealized geometries and seven adult male and female voxel models. The geometries are broad parallel photon beams in anterior-posterior, posterior-anterior, left- and right-lateral direction and a full 360 degree rotation around the body length axis. Dose differences between the different voxel models are below approximately 30% for some organs and geom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
118
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(129 citation statements)
references
References 15 publications
8
118
1
2
Order By: Relevance
“…Moreover, the reference values were calculated for the PCXMC phantom with standard dimensions, which corresponds to a patient size between XS and S (see Tables 1 and 2). For comparison, in the energy range between 60 and 200 keV, the range of variation in breast doses between different voxel models have been found to be up to 84% in the PA projection of whole body irradiations [31].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the reference values were calculated for the PCXMC phantom with standard dimensions, which corresponds to a patient size between XS and S (see Tables 1 and 2). For comparison, in the energy range between 60 and 200 keV, the range of variation in breast doses between different voxel models have been found to be up to 84% in the PA projection of whole body irradiations [31].…”
Section: Discussionmentioning
confidence: 99%
“…In that model the surface of the body is not represented in a realistic manner, and that may result in greater sensitivity to body size than the voxel models might indicate. As noted above, however, Zankl et al (2002) have observed dose differences as large as 100% among voxel models of adults. Calculations have not been reported for a sufficient number of voxel models of children to quantify the contribution of these anatomical models to uncertainties in the dose coefficients.…”
Section: Variation Of External Dose With Body Sizementioning
confidence: 93%
“…A voxel phantom is typically based on a living adult who is undergoing a scan for medical purposes but sometimes is based on a cadaver. Zankl et al (2002) used seven adult male and female voxel models to examine intersubject variability of tissue doses for external whole body irradiation by photons of energies between 10 keV and 10 MeV. The idealized geometries considered were broad parallel photon beams in anterior-posterior, posterior-anterior, left-and right-lateral direction and a full 360 degree rotation around the body length axis.…”
Section: The External Dose Model Of Fgr12mentioning
confidence: 99%
“…There are other phantoms in the GSF library, but only partial information about these has so far been published. Helga (head to mid-thigh) and Irene (whole body) are two female adult phantoms and Frank (head and trunk) and Visible Human (head to knee) are two male adult phantoms (Petoussi-Henss et al, 2002;Zankl et al, 2002). A mode1 of the female digestive system has also been voxelized, as an important area from a dosimetric point of view, particularly for intemal exposure.…”
Section: Donnamentioning
confidence: 99%
“…The authors of this work therefore recommend the use of voxel phantoms the size of whose organs is representative of the population under study, since the SAF is very dependent on the mass of the organs. For external dosimetry, the GSF team worked on establishing air kerma-to-dose conversion coefficients for exposure to photon beams in Baby and Child (especially for radiology examinations), Donna, Golem and Visible Human Zankl, 1992, 1993;Zankl et al, 1988Zankl et al, ,1995aZankl et al, , 1995bZankl et al, , 2002. The results were compared to those from the reference mathematical models from the new-born child, from the 10-year-old child , from Eva and from Adam.…”
Section: Donnamentioning
confidence: 99%